Protective Effect and Mechanism of Total Flavones from Rhododendron simsii Planch on Endothelium-Dependent Dilatation and Hyperpolarization in Cerebral Ischemia-Reperfusion and Correlation to Hydrogen Sulphide Release in Rats - Han, Jun; Chen, Zhi-Wu; He, Guo-Wei (Evidence-based complementary and alternative medicine, 2014)
We for the first time investigated the effect and mechanism of the total flavones of Rhododendron simsii Planch (TFR), a widely-used Chinese herb for a thousand years, on vasodilatation and hyperpolarization in middle cerebral artery (MCA) of rats subject to global cerebral ischemia-reperfusion (CIR). TFR (11~2700 mg/L) evoked dose-dependent vasodilation and hyperpolarization in MCA of both sham and CIR that were partially inhibited by 30 μM N-nitro-L-arginine-methyl-ester and 10 μM indomethacin and further attenuated by endogenous H2S synthese-CSE inhibitor PPG (100 μM) or Ca2+-activated potassium channel ( K ca ) inhibitor TEA (1 mM). In whole-cell patch clamp recording, TFR remarkably enhanced the outward current that was inhibited by TEA. CIR increased CSE mRNA expression and the contents of H2S that were further increased by TFR. We conclude that, in MCA of CIR rats, TFR induces non-NO and non-PGI2-mediated effects of vasodilatation and hyperpolarization involving K ca and increases CSE mRNA expression level in endothelial cells and H2S content in the cerebrum. These findings suggest that the response induced by TFR is potentially related to endothelium-derived hyperpolarizing factor mediated by the endogenous H2S and promote the use of TFR in protection of brain from ischemia-reperfusion injury.